2017
DOI: 10.1016/j.cimid.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus infection in horses, Indian ocean

Abstract: The circulation of West Nile virus (WNV) in horses was investigated in the Southwest Indian ocean. In 2010, blood samples were collected from a total of 303 horses originating from Madagascar, Mauritius, Reunion and the Seychelles and tested for WNV-specific antibodies. An overall seroprevalence of 27.39% was detected in the Indian Ocean with the highest WNV antibody prevalence of 46.22% (95% CI: [37.4-55.2%]) in Madagascar. The age and origin of the horses were found to be associated with the WNV infection ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…To our knowledge, this survey constitutes the first evidence of WNV and USUV circulation in the IND, Mali, and in the Lake Alaotra region, Madagascar-and the first estimation of WNV and USUV seroprevalence in domestic and/or wild birds in these regions. Several studies have already highlighted that WNV was endemic in Madagascar [53], with an antibody prevalence of 46.2% ([37.4-55.2%] 95%CI ) in horses sampled in 2010 in the Highlands [54], and of around 20% in the human population, mainly sampled in and around Antananarivo, the capital city of Madagascar [55]. Our results clearly show that WNV is circulating in the Lake Alaotra region.…”
Section: Discussionsupporting
confidence: 63%
“…To our knowledge, this survey constitutes the first evidence of WNV and USUV circulation in the IND, Mali, and in the Lake Alaotra region, Madagascar-and the first estimation of WNV and USUV seroprevalence in domestic and/or wild birds in these regions. Several studies have already highlighted that WNV was endemic in Madagascar [53], with an antibody prevalence of 46.2% ([37.4-55.2%] 95%CI ) in horses sampled in 2010 in the Highlands [54], and of around 20% in the human population, mainly sampled in and around Antananarivo, the capital city of Madagascar [55]. Our results clearly show that WNV is circulating in the Lake Alaotra region.…”
Section: Discussionsupporting
confidence: 63%
“…Cardinale et al. (2017) found that the older horses (between 11 and 15 years old) had the higher percentage of WNV antibodies, and Hassine et al. (2014) also observed that risk of WNV infection increased with the age of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the virus was considered of less human importance as it only caused mild, subclinical infections [ 7 ]. However, the virus has been responsible for many cases of morbidity and mortalities in different animal species, including birds [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], horses [ 6 , 18 , 19 ], sheep [ 20 ], reptiles [ 21 , 22 , 23 ], cats [ 24 ], and rodents [ 6 , 25 , 26 , 27 , 28 , 29 ]. Over the last two decades, there have been notable increases in human and equine cases.…”
Section: Introductionmentioning
confidence: 99%